2020
DOI: 10.1155/2020/3708730
|View full text |Cite
|
Sign up to set email alerts
|

The Preventive Effects of Asparagus officinalis Extract on Sodium Selenite‐Induced Cataractogenesis in Experimental Animal Models

Abstract: Background and Objectives. Cataract is the leading cause of blindness worldwide. Although surgery is now considered the most successful cure, the development of alternative treatments is needed due to postsurgical complications. Oxidative stress in the lens is considered to be the most crucial factor in the formation of cataracts. Therefore, the effects of the hydroalcoholic extract of Asparagus officinalis L, a traditional antioxidative plant, on cataract formation of sodium selenite were evaluated. Materials… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Low toxicity, availability and affordability of natural compounds has rendered them an alternative to stem cell therapies in regenerative medicine. Additionally, natural compounds have anti-inflammatory, wound healing and antioxidant activity in vivo which contributes to their application in tissue regeneration [16][17][18][19]. Studies have shown effective use of herbal medicines in treatment of various conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Low toxicity, availability and affordability of natural compounds has rendered them an alternative to stem cell therapies in regenerative medicine. Additionally, natural compounds have anti-inflammatory, wound healing and antioxidant activity in vivo which contributes to their application in tissue regeneration [16][17][18][19]. Studies have shown effective use of herbal medicines in treatment of various conditions.…”
Section: Introductionmentioning
confidence: 99%